2011
DOI: 10.1007/s00431-011-1479-5
|View full text |Cite
|
Sign up to set email alerts
|

PFAPA syndrome in siblings. Is there a genetic background?

Abstract: PFAPA syndrome is the most common recurrent periodic fever disorder described in childhood. Its genetic background has not been elucidated yet. Our contribution with two siblings affected with PFAPA syndrome further support the genetic basis for the entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 19 publications
(23 reference statements)
0
6
0
8
Order By: Relevance
“…PFAPA is classically considered as a sporadic and noninherited syndrome [ 8 ]; however, several studies reported PFAPA patients with family members having recurrent fever in their childhood [ 11 , 12 , 22 ]. In our cohort, we identified 3 pairs of siblings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PFAPA is classically considered as a sporadic and noninherited syndrome [ 8 ]; however, several studies reported PFAPA patients with family members having recurrent fever in their childhood [ 11 , 12 , 22 ]. In our cohort, we identified 3 pairs of siblings.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that PFAPA is considered as a sporadic disease, many studies suggest that it might have a genetic origin. Syndrome has overlapping symptoms with other PFSs with known genetic cause [ 11 ] and, furthermore, recurrent fever in the family members of PFAPA patients has been reported in several studies [ 10 , 12 ]. In addition, genetic variants that are known to cause other autoinflammatory syndromes have been found in PFAPA patients [ 9 , 13 ], but the impact of these genetic variants in PFAPA syndrome is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…An example is the PFAPA, which is not inherited as a mendelian trait, but does exhibit some familial tendency [54, 55]. While the exact cellular determinants and pathogenic molecular mediators remain elusive, the clinical picture and cytokine profile of PFAPA outline a very complex, heterogeneous, but nevertheless autoinflammatory, disease [55].…”
Section: Molecular Pathophysiology Of Pfssmentioning
confidence: 99%
“…Desde entonces se han publicado numerosos artículos de pacientes pediá tricos 7 y adultos 8,9 con la patología. En Españ a las series publicadas son relativamente escasas y con un nú mero reducido de pacientes 7,10,11 .…”
Section: Discusió Nunclassified